Gender Equality, Climate Action, and Technological Innovation for Sustainable Development in Africa - Adeola, Ogechi; Evans, Olaniyi; Ngare, Innocent; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2024)
This open access book explores the intersection of gender and climate change, suggests ways in which innovative technologies can accelerate climate relief actions, and offers strategies for integrating climate change initiatives into national policies and planning. By examining the devastating consequences of climate change on women and girls throughout the continent, the authors pose a crucial question: Does gender matter in climate change discussions in Africa? Political and social traditions have burdened women with greater vulnerability to the impacts of climate-related natural disasters, including violence, displacement, poverty, famine and lack of access to clean water. However, women are also key to effective and inclusive climate mitigation, adaptation, and decision-making. The authors provide a compelling discourse that identifi es the social and economic benefi ts for all citizens when genderinclusive policies shape equitable and targeted action plans, from mitigationto adaptation and funding. The UN$1 (Bs SDG 13 calls for urgent action and commitment to combat climate change. The implementable and action-oriented propositions presented in this book will be of interest to students, educators, practitioners, third-sector actors, and policymakers committed to gender equality, sustainable development and climate action in Africa.s
1: Introduction: Gender and climate change in Africa -- PART I: GENDER AND CLIMATE ISSUES IN AFRICA -- 2: Gender and Climate Issues in West Africa -- 3: Gender and Climate Issues in North Africa -- 4: Gender and Climate Issues in East Africa -- 5: Gender and Climate Issues in South Africa -- Part II: GENDER AND CLIMATE ACTION IN AFRICA -- 6: Strengthen resilience and adaptive capacity to climate-related hazards and natural disasters in Africa -- 7: Inculcation of SDG13 and gender inclusion in climate change policy frameworks and strategies in Africa -- 8: Women empowerment for climate change responsiveness in Africa -- PART III: GENDER, CLIMATE ACTION AND TECHNOLOGICAL INNOVATION -- 9: Digital technology and climate change adaptation in Africa -- 10: Climate-Smart Agriculture for navigating climate-related challenges of women in Africa$1 (Bs agricultural sector -- 11: Renewable energy (green ICT) for climate change mitigation and energy sustainability: The African challenge -- PART IV: CONCLUSION -- 12: Green reskilling of women for climate action -- 13: Conclusion: Towards Policy Synergy in Africa.s
Accessibility summary: This PDF does not fully comply with PDF/UA standards, but does feature limited screen reader support, described non-text content (images, graphs), bookmarks for easy navigation and searchable, selectable text. Users of assistive technologies may experience difficulty navigating or interpreting content in this document. We recognize the importance of accessibility, and we welcome queries about accessibility for any of our products. If you have a question or an access need, please get in touch with us at accessibilitysupport@springernature.com.
No reading system accessibility options actively disabled
Publisher contact for further accessibility information: accessibilitysupport@springernature.com
Keywords: Sex; Bioclimatology; Sustainability; Ethnology -- Africa; Culture; Technological innovations; Business; Africa; Gender Studies; Climate Change Ecology; Sustainability; African Culture; Innovation and Technology Management; African Business